Study on energy evolution and crack propagation of filling mortar-rock at different loading rates - Wang, Hanqiu; Liu, Chengyong; Wu, Yuyi; Guan, Yuhua; Zhao, Tongde (PloS one, 2025)
Shotcrete, as a highly efficient reinforcement material widely used in geotechnical engineering, demonstrates irreplaceable advantages in projects such as tunnel excavation, mine roadway support, and slope protection. However, when shotcrete becomes tightly bonded with rock masses, the energy evolution and crack initiation mechanisms between the two materials exhibit remarkable complexity. Different loading rates significantly alter the internal stress distribution and deformation characteristics within the composite system, thereby influencing the patterns of energy evolution and crack propagation. Consequently, it is essential to investigate the mechanical behavior of filling mortar-rock under varying loading rates. Firstly, uniaxial tests with four loading rates were conducted for the composite specimens, and the effects of loading rate on the mechanical parameters, energy evolution and fracture modes were analyzed. The results show that the mechanical parameters of the composite decrease with the rise of loading rate, and the decrease reaches the maximum when the mortar strength is M20. All three types of energies decreased exponentially with increasing loading rate. The decrease reaches the maximum at a mortar strength of M40. Subsequently, a damage model applicable to the composite specimens was established based on the development rules of the dissipated energy and the compaction coefficient. Finally, PFC 2D was used to simulate and analyze the specimens with mortar grade of M30 to investigate the crack propagation and stress evolution process at four loading rates. The results show that tensile stress is the causative factor of crack propagation. The cracks first appeared at the interface, and were mainly distributed on both sides of the specimen after cracking.